The Influence Of Online Customer Review On Purchase Decision Through Mediation Of Perceived Service Quality In The Shopee Marketplace For Fashion Products In Makassar - Nadia Elizabeth Wijaya; Irene Angelica Siwu; Christine Audrey Thompson; Andi Siti Nuraisyah Rahman; Aracel Nestovani Sutanto; Asriah Syam (Accounting Profession Journal (APAJI), 2026)
The advancement of digital technology has reshaped consumer behavior, especially through e-commerce platforms. Indonesia, with its large number of internet users, shows rapid growth in online shopping, particularly for fashion products. This study analyzes the effect of Online Customer Reviews (OCR) on Purchase Decision, with Perceived Service Quality (PSQ) as a mediating variable, using the Stimulus-Organism-Response (S-O-R) framework. Data were collected from 268 active Shopee users in Makassar who had purchased fashion items in the last three months. Analysis using WarpPLS 8.0 revealed that OCR significantly affects both Purchase Decision and PSQ. However, PSQ did not mediate the relationship between OCR and Purchase Decision. The findings suggest that consumer reviews play a direct role in shaping purchase decisions. Therefore, sellers on Shopee are encouraged to promote review activity from customers to improve trust and drive future sales.